2011 IEEE 23rd International Symposium on Power Semiconductor Devices and ICs 2011
DOI: 10.1109/ispsd.2011.5890865
|View full text |Cite
|
Sign up to set email alerts
|

Design and characterization of a signal insulation coreless transformer integrated in a CMOS gate driver chip

Abstract: Design and characterization of a signal insulation coreless transformer integrated in a CMOS gate driver chip. Design and characterization of a signal insulation coreless transformer integrated in a CMOS gate driver chip, Abstract-With the development of multi-level, multiphase or network converters requiring the implementation of numerous distinct power transistor gate drivers, the control signal insulation is becoming more and more important in power converters. This paper presents an isolation technique bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…We confirmed that the observed delay of several microseconds mostly occurred in the gate driver. In our future work we plan to use our technology to supply power to the IGBT gate driver and integrate the power supply with the signal transmission (13) (14) .…”
Section: Measurement Of Insulated Communication Modulementioning
confidence: 99%
“…We confirmed that the observed delay of several microseconds mostly occurred in the gate driver. In our future work we plan to use our technology to supply power to the IGBT gate driver and integrate the power supply with the signal transmission (13) (14) .…”
Section: Measurement Of Insulated Communication Modulementioning
confidence: 99%
“…On the other hand, while transformers are widely used for power isolation, the bulky size and the high cost of conventional transformers make them unfavorable for signal isolation. In this century, by miniaturization and integration of transformers onto silicon chips for size and cost reduction, microtransformers are receiving increasing interest for signal [3][4][5][6][7][8][9][10][11][12] and power [13][14][15][16][17] isolation applications. Compared to optocoupler based signal isolation, micro-transformer based signal isolation provides faster speed, lower power consumption, and longer lifetime, and therefore has already been taking an increasing market share.…”
Section: Introductionmentioning
confidence: 99%
“…To relax the signal transfer quality requirement of micro-transformers, digital signal isolation with various signal encoding and decoding schemes have been proposed so that the micro-transformers only need to transfer encoded high frequency pulses, with an example shown in Fig.1. With such techniques, signal isolation has been successfully implemented using micro-transformers with < 0.5 mm 2 sizes and relatively poor voltage gains [5][6][7][8][9][10][11][12]. However, as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Engineers and scientists have produced a huge variety of solutions ranging from transformers to optical systems links. Recently coreless transformers have gained popularity as it is now possible to integrate them with driver integrated circuits, [4,5,1]. For some applications especially or when full integration is not practical, it could be advantageous to have a discrete integrated coreless component.…”
Section: Introductionmentioning
confidence: 99%